2008
DOI: 10.1242/dev.016295
|View full text |Cite
|
Sign up to set email alerts
|

APC/CFzr/Cdh1 promotes cell cycle progression during theDrosophilaendocycle

Abstract: The endocycle is a commonly observed variant cell cycle in which cells undergo repeated rounds of DNA replication with no intervening mitosis. How the cell cycle machinery is modified to transform a mitotic cycle into endocycle has long been a matter of interest. In both plants and animals, the transition from the mitotic cycle to the endocycle requires Fzr/Cdh1, a positive regulator of the Anaphase-Promoting Complex/Cyclosome (APC/C). However, because many of its targets are transcriptionally downregulated up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
97
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 80 publications
(147 reference statements)
3
97
0
Order By: Relevance
“…Kolpakas, S. Maqbool, and B. Calvi, unpubl.). Moreover, previous evidence suggested that the Dup inhibitor Geminin, and periodic inhibition of CDK2, is important for normal endocycle DNA replication (Hong et al 2007;Narbonne Reveau et al 2008;Zielke et al 2008). It is possible, however, that some aspects of the origin licensing mechanism differ between mitotic cycles and endocycles.…”
Section: Rereplication Is Distinct From the Normal Process Of Endoredmentioning
confidence: 99%
“…Kolpakas, S. Maqbool, and B. Calvi, unpubl.). Moreover, previous evidence suggested that the Dup inhibitor Geminin, and periodic inhibition of CDK2, is important for normal endocycle DNA replication (Hong et al 2007;Narbonne Reveau et al 2008;Zielke et al 2008). It is possible, however, that some aspects of the origin licensing mechanism differ between mitotic cycles and endocycles.…”
Section: Rereplication Is Distinct From the Normal Process Of Endoredmentioning
confidence: 99%
“…At the molecular level, endoreduplication is likely achieved through elimination of the components needed to progress through mitosis (11). Predominant roles in this process are played by the anaphase-promoting complex/cyclosome (APC/C) activator genes, such as CDH1, FZR, and CCS52A, which have been found to promote endocycle onset and progression in human, Drososphila melanogaster, and Medicago truncatula cells, respectively (12)(13)(14)(15)(16)(17). The mechanisms controlling the transcriptional activity of these genes remain unclear, however.…”
mentioning
confidence: 99%
“…However, the entry into and the progression through endoreplication cycles do not necessarily have to be regulated by the same molecular mechanism. Nonetheless, it has recently been found that APC/C also controls progression through endoreplication cycles in Drosophila by targeting the replication inhibitor Geminin for degradation (16,17). However, Geminin is not present in all organisms and so, for instance, no Geminin ortholog could be thus far isolated from plants.…”
mentioning
confidence: 99%